Effect of Loci-Kit Models on Students Academic Performance in Technical Drawing in Edo State Technical Colleges, Nigeria - Jane Itohan Oviawe; Patrick S.O. Uddin (Universitas Ahmad Dahlan, 2020)
The study investigated the effect of loci-kit models on students academic performance in technical drawing in Edo State technical colleges using non-equivalent control group quasi-experimental research design. Two research questions and two null hypotheses guided the study. The population for this study consisted of 864 vocational II students from the six technical colleges in Edo State. The sample for the study comprised of 110 (60 males and 50 females) randomly selected from all the technical colleges in Edo State. The instrument for data collection was Technical Drawing Achievement Test (TDAT). Three experts validated the instrument. The reliability of the instrument was determined using Kuder Richardson 21 (KR-21) formulae and a reliability coefficient of .85 was obtained. The research questions were answered using Mean and standard deviation while Analysis of Covariance (ANCOVA) was used to test the hypotheses at .05 level of significance. Findings from the study revealed that Loci-kit model was effective in enhancing technical college students performance in technical drawing topic loci; there was no significant mean effect of gender on students Mean performance score in Technical Drawing. In line with the findings of the study, it was recommended among others that Technical Drawing teachers should employ innovative approaches such as loci-kit models during instructions of loci concepts in technical drawing to facilitate students academic performance in the subject.